The predictive value of γ-glutamyl transferase to serum albumin ratio in hepatocellular carcinoma patients after liver transplantation - Luo, Xing-Yu; Chang, Kai-Wun; Ye, Nan; Gao, Chen-Hao; Zhu, Qing-Bo; Liu, Jian-Peng; Zhou, Xing; Zheng, Shu-Sen; Yang, Zhe (Frontiers in Medicine, 2024)
Background: Elevated preoperative γ-glutamyl transferase (GGT) levels or reduced serum albumin levels have been established as negative prognostic factors for patients with hepatocellular carcinoma (HCC) and various other tumors. Nonetheless, the prognostic significance of the GGT to serum albumin ratio (GAR) in liver transplantation (LT) therapy for HCC is still not well-defined.A retrospective analysis was conducted on the clinical data of 141 HCC patients who underwent LT at Shulan (Hangzhou) Hospital from June 2017 to November 2020. Using the receiver operating characteristic (ROC) curve, the optimal GAR cut-off value to predict outcomes following LT was assessed. Univariate and multivariate Cox proportional hazards regression analyses were employed to identify independent risk factors associated with both overall survival (OS) and recurrence-free survival (RFS).Results: A GAR value of 2.04 was identified as the optimal cut-off for predicting both OS and RFS, with a sensitivity of 63.2% and a specificity of 74.8%. Among these patients, 80 (56.7%) and 90 (63.8%) met the Milan and the University of California San Francisco (UCSF) criteria, respectively. Univariate Cox regression analysis showed that microvascular invasion (MVI), maximum tumor size (>5cm), total tumor size (>8cm), liver cirrhosis, TNM stage (Ⅲ),and GAR (  2.04) were significantly associated with both postoperative OS and RFS in patients with HCC (all P<0.05). Multivariate Cox regression analysis indicated that GAR (  2.04) was independently linked with RFS and OS.